Dietary Assessment and Food Intake In Elderly Individuals Attending Public Health Centers In Urban Areas of Baghdad City In Iraq . - AlSharbaty, Shatha S.; hameed., Wameedh A . (Journal of the Faculty of Medicine Baghdad, 2013)
Background: The population composition in all countries is changing very rapidly, with the result that there will now be Increasing numbers of elderly in all communities and in all countries of the world .Age-related changes in body habits, and disease and medication-related interactions can affect the nutritional requirements of elderly persons. This can further compounded by difficulties that older persons experience in accessing grocery stores and in cooking healthy food Many older persons relay on the convenience of buying processed foods or ordering fast food that can contribute to both obesity and deficiencies in essential nutritional requirements . The diagnosis of nutritional deficiency states in elderly people is made more difficult by the usual symptoms and signs being masked by diseases. Objectives: To assess the dietary and food intake in a sample of elderly subjects. Patients and methods: A random sample of 184 elderly persons were included in the study 58.2% males and 41.7% females selected randomly from a list of public health centers in urban areas of Baghdad city , it was carried out during the period between the first of March and the end of August 2005. Results: Highest proportion of the studied males and females aged 65-74years, the total number of males and females in this age group constitute (65.8%) of the studied sample. The highest frequency of elderly subjects with inadequate dietary intake was observed in vitamin B12 (59.2%) .The frequency of inadequate dietary intake was higher among elderly females than that in males for energy 28.6%, iron 18.2%,vitamin C 54.5%, vitamin B1262.3%, while it was higher among elderly males for protein 13.1%. It was found that high proportion of the studied sample had mean food daily intake less than the recommended mean values for milk 98.4% , vegetables 97.3% , fruits 96.7% , fish and sea food 95.1% . Furthermore 70.7%, of the studied elderly subjects had mean food daily intake less than the recommended mean values of meat/poultry, legumes 59.3% , egg and products 57.6% respectively , while 88% of them had high recommended mean food daily intake of cereals. The mean ± SD of BMI of elderly subjects of present study was 27.6 ± 4.8 . Conclusion: The mean food daily intake of milk , meat/poultry/fish ,vegetables and fruits are deficient in a high proportion of the studied elderly subjects .Acceptable percentage of the studied sample had high mean food daily intake of cereals .The frequency of inadequate dietary intake was higher for energy , iron ,vitamin c, vitamin b12 in the study sample .